Evidence for an increase in cannabis use in Iran - A systematic review and trend analysis. - Yasna Rostam-Abadi (Public Library of Science (PLoS), 2021)
Background and aims Cannabis is the most widely used illicit substance globally. In this systematic review, we examined the prevalence and trends of cannabis use and cannabis use disorder in Iran. Methods We searched International and Iranian databases up to March 2021. Pooled prevalence of use among sex subgroups of the general population, university and high school students, combined youth groups, and high-risk groups was estimated through random-effects model. Trends of various use indicators and national seizures were examined. Results Ninety studies were included. The prevalence estimates of last 12-month cannabis use were 1.3% (95%CI: 0.1-3.6) and 0.2% (95%CI: 0.1-0.3) among the male and female Iranian general population, respectively. The prevalence of cannabis use disorder among general population in national studies rose from 0% in 2001 to 0.5% in 2011. In the 2016-2020 period, the pooled prevalence estimates of last 12-month cannabis use were 4.9% (95% CI: 3.4-6.7) and 0.3% (95% CI: 0.0-1.3) among males and females of "combined youth groups", respectively. The linear trend of last 12-month cannabis use among males of "combined youth groups" and among female university students increased significantly from 2000 to 2020. Conclusions Prevalence of cannabis use in Iran is low compared to many countries. However, there is strong evidence of an increase in cannabis use among the youth and some evidence for an increase in cannabis use disorder.